2011
DOI: 10.1055/s-0031-1293204
|View full text |Cite
|
Sign up to set email alerts
|

Does Obesity Increase the Risk of Miscarriage in Spontaneous Conception: A Systematic Review

Abstract: Obesity has become an epidemic in developed societies. Retrospective studies suggest that obesity is associated with miscarriage in assisted reproduction. The objective of this study was to evaluate whether obesity is associated with miscarriage in spontaneous conception. We conducted a systematic review of published studies with pooled analysis. A literature review was performed. Studies in which fertility drugs or in vitro fertilization were used were excluded, unless data could be extracted for spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
1
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(150 citation statements)
references
References 29 publications
5
129
1
15
Order By: Relevance
“…Obesity is known to have an impact on the hypothalamic-pituitary ovarian axis, and on oocyte, embryo and endometrial development, including implantation [30], with larger women being shown to have a higher miscarriage rate compared to woman with a normal BMI [7]. PCOS is more common in obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is known to have an impact on the hypothalamic-pituitary ovarian axis, and on oocyte, embryo and endometrial development, including implantation [30], with larger women being shown to have a higher miscarriage rate compared to woman with a normal BMI [7]. PCOS is more common in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight or obese women are more likely to suffer from oligomenorrhoea. They have also been shown to have a higher risk of miscarriage than the background population; a miscarriage rate of 13.7% has been documented in obese women, compared to 10.9% in women with a normal BMI [7]. The recurrent miscarriage rate has also been speculated to be increased in obese women, however, a recent systematic review has not confirmed this [7].…”
Section: Bmi and Natural Conceptionmentioning
confidence: 99%
“…Проблема не только забеременеть, но и выносить беременность. Согласно систематиче-скому обзору мета-анализа исследования по проблеме ожирения и риска самопроизвольного выкидыша, оказалось, что среди женщин, забеременевших спон-танно, частота риска возникновения выкидыша у женщин с ожирением выше, чем у женщин с нор-мальным весом [21]. По данным мета-анализа 2015 г. выявлено, что риск осложнений беременности повы-шается по мере увеличения ИМТ.…”
Section: влияние ожирения на репродукциюunclassified
“…Протеомный анализ образцов эндометрия у пациенток с различной массой тела показал нарушение экспрессии лейкемие-инте-грирующего фактора и гаптоглобина, что может объ-DOI: 10.14341/OMET2017416-22 Ожирение и метаболизм. 2017;14(4): [16][17][18][19][20][21][22] О б з о р ы л и т е р а т у р ы яснить высокую частоту прерывания беременности на раннем сроке [38]. В работах других авторов выяв-лена положительная корреляция между повышенным ИМТ и увеличением толщины эндометрия, что также может влиять на изменение его рецептивности [39].…”
Section: ожирение как предиктор неудач в программах вспомогательных рunclassified
“…Obesity is associated with many endocrine disorders, such as diabetes, hypothyroidism, and PCOS, which theoretically could result in an increased risk of euploid miscarriage due to suboptimal implantation related to endocrine changes. [83] completed a systematic review evaluating whether obesity increases the rate of miscarriage in spontaneously conceived pregnancies. The odds of having RM were increased for obese women (odds ratio [OR] 1.31, 95% CI 1.18-1.46) and overweight women (OR 1.11, 95% CI 1.00-1.24), when compared with women with normal BMI.…”
Section: Hormonal and Metabolic Etiologymentioning
confidence: 99%